Heat Transfer Analysis of Thermal Oil Plant on Fuel Oil Tanks of 17500 LTDW Product Oil Tanker - Taufik Fajar Nugroho; Wolfgang Busse; Ede Mehta Wardhana; Juda Imanuel Osvaldo Panggabean (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2018)
The thermal oil system is one type of heater that widely used on ships. The system is an important system used to heat fuel that will be used for the operation of the main engine, auxiliary engine, and boiler. This system has been installed on 17500 LTDW Product Oil Tanker, MT. Parigi, but not yet tested so that it does not know whether the system is able or not to transfer heat from heating equipment (boiler and economizer) to each fuel tank in accordance with the desired value. Therefore, this research performs an engineering evaluation in term of heat transfer analysis to ensure that the heat transfer process of thermal oil from heating equipment to the fuel tanks is already meeting the required temperature or not. This analysis is done by using thermodynamic equation, namely heat balance equation and heat loss equation. The result shows that the heat transfer of thermal oil to each fuel tank corresponds to the desired value, namely 180oC for the thermal oil inlet temperature to each fuel tank and 140oC for the thermal oil re-enter temperature to the heating equipment.